2024 Election And Identity Politics - Auderey G. Tangkudung, Rizqita Oktorini, Fera Belinda, Jemmy Kaseger (Novateur Publications, 2022)
This study discusses how identity politics is very influential in the 2019 presidential election and its challenges in facing the 2024 election. The development of Indonesian democracy as reflected in the presidential election still faces many problems. This means that the polarization of identity politics is used by a handful of political elites and parties to win their candidates in the presidential election and regional head elections. As a party or a good political elite, the task is how to create a democratic atmosphere that is beneficial, orderly and beneficial for many people. The deepening of democracy has not been carried out properly because the pillars of democracy which are the strengthening factors of democracy have not been effective. The survey method uses a qualitative descriptive approach. Research shows that the 2019 presidential election failed to demonstrate a series of excellent democratic practices and build public trust. This can be seen from the emergence of unrest in the community and social problems, namely the emergence of prolonged conflicts as a result of the use of identity politics in the election of President and regional heads and this has resulted in a very disturbed sense of unity and integrity as a nation. Therefore, it is necessary to take strategic steps to reduce the impact of conflicts that can occur. What is being done is to strengthen national identity. National identity can be a powerful ingredient in re-gluing a polarized society and becoming an antidote to divisions that may occur. Indonesia's national identity needs to be built and disseminated in society, an opportunity for people with sufficient knowledge of national identity to build a strong society against polarization and provocation. Thus the implementation of the 2024 presidential and regional elections will be carried out properly and identity politics will be abandoned by the community by itself.
Keywords: 2024 Election & Identity Politicization.